THE Advancement of Digital Text Reading Perceived by Indonesian EFL Students Amid the Pandemic Covid-19 - Ari Safar Wadi; Ab. Aziz Bin Sulaiman; Roi Boy Jon; Hizbul Wathoni (ITScience (Information Technology and Science), 2022)
Reading is one of the essential English skills to understand written information in all available sources. In recent days, reading is not merely found in printed forms but also can be accessed in digital matters. During the pandemic COVID-19 era, digital text reading is highly required rather than printed issues. In the Indonesian context, digital reading is increasingly needed as the replacement for physical learning activities to cut the COVID-19 spreads. However, there have been a lot of views regarding the use of digital text to promote English reading instruction. This study discusses the advancement of digital text reading coped with Indonesian EFL students during the pandemic COVID-19. This study addressed a systematic literature review to illustrate the enhancement of digital text reading among Indonesian EFL students during COVID-19. Using the systematic literature review, the researcher arranged the study's data through various previous studies discovering the use of digital text reading. The present study's findings describe several issues related to the advancement of digital text reading encountered by Indonesian EFL learners amid the pandemic. The study demonstrates online reading among Indonesian EFL students, teachers' and students' perception of online homework, digital reading strategies in ELT, and the impact of digital design on English reading activities and comprehension.